Lithuanian National Regional Policy and Preconditions for its Implementation - Pareigis, Rimantas; Dorofejeva, Oksana (Ekonomika, 2004)
Regional development can be treated as development of community’s social, economic, environmental, health protection, cultural, technological and recreational issues on the particular location or site. Regional development can be defined as the set of policy measures aiming to enhance economic development in the region by using efficiently all local resources. In this case for achieving the final target - increased economic development of the country the preference is allocated to the economic development, which is the major part of community development because guarantees supply of financial resources to community which is necessary for the implementation of all other issues of community development. The article deals with regional development problems arising in Lithuania during preparation to EU integration. The object of study models for the implementation of regional development policy. The aim of the article - to analyse regional development problems in Lithuania and to define possible models for the implementation of regional development policy in Lithuania seeking to ensure efficiency and integrity of regional development policy in Lithuania.